Condition factor and carapace width versus wet weight relationship in the blue swimming crab Portunus segnis - Moghaddam, Parvaneh; Kalvani Neitali, Bita; Kamrani, Ehsan; Noori, Ahmad; Pinheiro, Marcelo Antonio Amaro [UNESP]; Akbarzadeh, Arash (Brill Academic Publishers, 2015)
The size-weight relationship of a species allows for estimating the expected weight based on size the present contribution aims at evaluating the body weight vs. carapace width relationship and the condition factor of the blue swimming crab Portunus segnis these characteristics were analyzed for each sex using specimens collected monthly from April 2012 through to March 2013, at the Persian Gulf (Hormozgan Province, Iran) the size of each specimen was measured (carapace width) and weighed (total body wet weight). A total of 302 individuals of P. segnis were analyzed the body weight-carapace width relationship indicated positive allometric growth in males and isometric growth in females. Body weight was higher in males than females of equivalent carapace width, and the means for condition factors were always higher in females than in males, due to the heavier gonads in the former, an expected pattern for many crabs. In both sexes, the lowest condition factor was detected in winter with an ascending trend in the next seasons the oscillation in condition factor throughout the sampling year was more prominent in females and related to the reproductive cycle the information reinforces data to define fishing closed seasons for this portunid that is used in many places in the world.
Keywords: Biometry; body size; condition factor; crab; gonad; reproduction; weight